2009
DOI: 10.4102/sajip.v35i1.753
|View full text |Cite
|
Sign up to set email alerts
|

Fluid intellingence and spatial reasoning as predictors of pilot training performance in the South African Air Force (SAAF)

Abstract: <p>Pilot selection is a form of high-stakes selection due to the massive costs of training, high trainee ability requirements and costly repercussions of poor selection decisions. This criterion-related validation study investigated the predictive ability of fluid intelligence and spatial reasoning in predicting three criteria of pilot training performance, using an accumulated sample of South African Air Force pilots (<em>N </em>= 108). Hierarchical multiple regression analyses with training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…These estimates had the least variability around the means, indicating that spatial ability–flight performance relations are relatively homogeneous. Spatial ability is frequently presented as a vital ability for proficient flying performance, and numerous studies have been conducted to validate its importance for training flight performance (e.g., Barron and Rose, 2013; Johnson et al, 2017; Kock & Schlechter, 2009; Zierke, 2014). It may be surprising, then, to detect these modest validity estimates for spatial subtests relative to those produced by technical knowledge, perceptual speed, and quantitative abilities subtests.…”
Section: Discussionmentioning
confidence: 99%
“…These estimates had the least variability around the means, indicating that spatial ability–flight performance relations are relatively homogeneous. Spatial ability is frequently presented as a vital ability for proficient flying performance, and numerous studies have been conducted to validate its importance for training flight performance (e.g., Barron and Rose, 2013; Johnson et al, 2017; Kock & Schlechter, 2009; Zierke, 2014). It may be surprising, then, to detect these modest validity estimates for spatial subtests relative to those produced by technical knowledge, perceptual speed, and quantitative abilities subtests.…”
Section: Discussionmentioning
confidence: 99%
“…For example, longitudinal studies of selected high‐ability students (Shea, Lubinski, & Benbow, ; Webb, Lubinski, & Benbow, ) and representative samples of the general youth population (Wai, Lubinski, & Benbow, ) have found that spatial ability adds incremental validity beyond math and verbal ability (e.g., SAT‐Math and SAT‐Verbal) in predicting attainment of undergraduate and graduate degrees in STEM and subsequent STEM careers and achievements (e.g., publications and patents). Consistent with these findings, spatial ability measures have shown incremental validity beyond fluid intelligence for predicting performance in STEM domains (dentistry: Hegarty, Keehner, Khooshabeh, & Montello, ; surgery: Keehner, Lippa, Montello, Tendick, & Hegarty, ; piloting: de Kock & Schlechter, ).…”
Section: Introductionmentioning
confidence: 70%
“…These reviews and other studies (e.g., de Kock & Schlechter, 2009; Olea & Ree, 1994; Ree & Carretta, 1996; Zierke, 2012) have shown intelligence and cognitive functioning to be crucial to pilot training performance. Several other constructs have demonstrated incremental validity when used in combination with measures of intelligence/cognitive functioning.…”
Section: Introductionmentioning
confidence: 89%
“…All statistical analyses used a .05 Type I error rate and one-tailed tests. One-tailed tests were used as results from prior studies have consistently shown cognitive ability to be positively related to pilot training outcomes (e.g., Carretta & Ree, 2003; de Kock & Schlechter, 2009; Ree & Carretta, 1996; Zierke, 2012).…”
Section: Methodsmentioning
confidence: 99%